Improvement in patient outcomes following endovascular treatment of WFNS grade V subarachnoid haemorrhage from 2000 to 2014. (May 2016) - Inamasu, Joji; Sadato, Akiyo; Oheda, Motoki; Hayakawa, Motoharu; Nakae, Shunsuke; Ohmi, Tatsuo; Adachi, Kazuhide; Nakahara, Ichiro; Hirose, Yuichi
Highlights: Patient outcomes following grade V subarachnoid haemorrhage (SAH) had been dismal. Whether endovascular treatment (EVT) improved outcomes chronologically was studied. Patients (n = 115) were trichotomised (2000–04, n = 44; 2005–09, n = 37; 2010–14, n = 34). Mortality rate was significantly lower in 2000–04 than that in 2010–14 (52% vs. 24%). EVT may be a viable treatment option for grade V SAH patients in terms of survival. Abstract: Patient outcomes following grade V subarachnoid haemorrhage (SAH) have been dismal, although they may have improved following recent technological advances in endovascular treatment (EVT). A single-centre, retrospective study was conducted to evaluate whether outcomes have improved from 2000 to 2014 for patients with World Federation of Neurosurgical Societies (WFNS) grade V SAH. Coiling has been the preferred first-line treatment for grade V SAH patients in our institution since 2000. Patients who underwent EVT (n = 115) were grouped on the basis of their hospital admission year: 2000–2004 (n = 44), 2005–2009 (n = 37) and 2010–2014 (n = 34). Patient demographics, outcomes and in-hospital mortality rates were compared between the groups. Patient outcomes at discharge were evaluated using the Glasgow Outcome Scale (GOS), with GOS scores of 4–5 defined as favourable outcomes. There were no significant intergroup differences in patient demographics. In addition, there were no significant differences in the frequencies of favourable outcomes (14% in 2000–2004, 16% in 2005–2009 and 26% in 2010–2014). Mortality rates were 52% in 2000–2004, 43% in 2005–2009 and 24% in 2010–2014, with a significantly lower mortality rate in 2010–2014 than in 2000–2004 ( p  = 0.01). Both perioperative rebleeding and delayed cerebral ischaemia decreased over time; however, multivariate regression analysis showed that the former contributed more to the decrease in mortality. Age was the only variable associated with favourable outcomes. The results of this study indicate that EVT is an appropriate therapeutic option for grade V SAH patients. However, multi-centre, prospective trials are required to provide evidence-based verification of the efficacy of EVT.